A CNBB no contexto da globalização: a instituição religiosa como agente de mobilização nacional e de ação político-social - Salomão, Norberto (2005)
This dissertation tried to establish the CNBB action in the context of globalization at a clear and objective way, in the face of deep and quick transformations that are happening at our time. This way, we dedicate ourselves to do a historic of the behavior of the Catholic Church in Brazil until nowadays, when, making use of several references, we demonstrate the declared institution s option to poor people, in national and international scope. That posture is reinforced by the entity s declarations and actions, which allied to other organized sectors of society, harmonize politics and religion. We got as fundamental references to these actions: the plebiscite of 2000 against the payment of the external debit and the plebiscite of 2002 against FTAA (Free Trade Area of de Americas), trying to demonstrate how a religious institution is able to establish itself as an agent of national mobilization and of political and social actions. We understand that more than the shown goals, the religious entities, specifically the Brazilian Catholic Church, making use of the CNBB and its pastorals, want to keep their importance and influence, being up-to-date in their speech and in their actions in an uncertainty era.